Shari'aa supervision on Islamic banks in the light of economic transformations - Al Deek, Mohammed Yousef (Arab Journal for Sciences and Research Publishing, 2016)
In this research is marked by censorship legitimate and which are based on the follow-up of economic activity of Islamic banks by suitable means until we are sure of the work in accordance with the principles of religion Shara, and in order to keep pace with the rapid developments and sudden changes. It highlighted the importance of the Sharia Supervisory basic requirements escort this shift represented in the prestigious and legitimate autonomy of the work committed to the purposes Sharia Supervisory Board without inertia of sergeant when contracts form the qualities and work to raise public awareness of the nature of the banking business and practice of corporate governance as a principle backer of the safety of the banking system and be a supreme body as a reference to senior oversight bodies Note legitimacy with arms culture of applicable law and should such control be integrated and comprehensive in its various stages
Keywords: Sharia supervision; economic transformations; Islamic banks